Le pouvoir économique du Chinatown de Londres : d’un espace de l’entre-deux à un produit londonien - Quôc-Dung DANG (E-REA)
First created to nestle immigrants who had left their countries, mostly from Hong Kong and China, London’s Chinatown (near Soho) progressively allowed for the emergence of a transitional space, a medium, or a place in-between which helped those immigrants to adapt to the new habitat. Gradually, the cultural and economic landscape of London’s Chinatown has become an attraction and Chineseness, an object of consumption for both local residents and outsiders. The place branding process of London’s Chinatown has contributed to creating new ways of reading the place, and is not only carried out by the Chinese as some form of self-fashioning, but also by local authorities, networks of associations and mostly Shaftesbury—a British real estate investment trust. Highly marketed as a commodity, London’s Chinatown has been re-imagined and transformed into a hybrid social, economic and political construct that is intrinsic to the West, and more particularly to London.